2019
DOI: 10.1002/oby.22607
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐State Brain Connectivity Predicts Weight Loss and Cognitive Control of Eating Behavior After Vertical Sleeve Gastrectomy

Abstract: Objective The effects of sleeve gastrectomy (SG) on functional connectivity (FC) and associations with weight loss and eating‐related cognitive control were investigated. Methods In a longitudinal study, 14 SG patients (13 female; 42.1 presurgery BMI) completed study visits 1 month pre surgery and 12 months post surgery. Patients completed the Dutch Eating Behavior Questionnaire and resting‐state functional magnetic resonance imaging scanning to measure FC. Data were analyzed using a seed‐to‐voxel approach in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…Many neuroimaging findings in RYGB subjects were often associated with self-reported exaggerated fullness and lower levels of appetite with altered food preferences ( Ochner et al, 2011 ; Hunt et al, 2016 ; Zoon et al, 2018 ; Baboumian et al, 2019 ). Similar brain imaging observations made after VSG ( Cerit et al, 2019 ). Furthermore, widespread structural and functional changes across the brain also take place after RYGB ( Rullmann et al, 2018 ) and VSG ( Michaud et al, 2020 ).…”
Section: Potential Mechanisms Leading To Phantom Satiationsupporting
confidence: 78%
“…Many neuroimaging findings in RYGB subjects were often associated with self-reported exaggerated fullness and lower levels of appetite with altered food preferences ( Ochner et al, 2011 ; Hunt et al, 2016 ; Zoon et al, 2018 ; Baboumian et al, 2019 ). Similar brain imaging observations made after VSG ( Cerit et al, 2019 ). Furthermore, widespread structural and functional changes across the brain also take place after RYGB ( Rullmann et al, 2018 ) and VSG ( Michaud et al, 2020 ).…”
Section: Potential Mechanisms Leading To Phantom Satiationsupporting
confidence: 78%
“…Some metabolic markers may predict weight regain after surgery (Abidi et al, 2019), also taste preference towards salty or sucrose-sweetened foods may contribute to some extent (Zhang et al, 2019; Smith et al, 2020). Our study is the first PET study to predict the outcome of bariatric surgery from neuroimaging markers, and only two small MRI studies exist (Holsen et al, 2018; Cerit et al, 2019). Our study shows that molecular organization of the brain’s reward circuit is an important determinant of the surgery-induced weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are only two small MRI studies that have investigated brain markers that might affect the weight loss outcome of the surgery. Functional connectivity and alterations in brain activity in some of the key areas of reward circuit predicted weight loss 12 months after sleeve gastrectomy (Holsen et al, 2018; Cerit et al, 2019). However, the role of specific neurotransmitter systems – such as D 2 R and MOR implicated in feeding and reward processing – on post-surgical weigh gain and loss remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has also shown that NAc functional connectivity with frontoparietal-accumbal may have some role in dopaminergic and reward systems of the brain [ 44 ]. As a result, the functional connectivity of the frontoparietal network and the NAc may have a role as a predictor factor for the BMI at baseline and change over time [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although NAc function is a well-established predictor of food-seeking behaviors [ 21 ], less is known about the role of connectivity between the NAc and frontoparietal network on obesity [ 37 , 38 , 39 , 40 , 41 ]. While we know that NAc function is different in obesity-prone individuals than others [ 26 , 27 , 28 , 29 , 30 , 31 ], there is a need for longitudinal epidemiological studies on the NAc-frontoparietal connectivity as a predictor of obesity risk at the population level [ 21 ].…”
Section: Introductionmentioning
confidence: 99%